Kegiatan Cooking Class dalam Meningkatkan Kemandirian dan Keterampilan Siswa - Faqih, Faqih Hakim Hasibuan; Dira Puspita Sari (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Student independence and skills are now a problem that can be solved. In today's digital age, student independence and skills must be increased. Based on the literature review carried out, researchers can conclude that cooking class is a fun activity for students and can increase students' independence and skills which are reflected in the cooking activities carried out by students with teachers at elementary schools. Through this study, it is hoped that teachers will be able to carry out cooking class activities for elementary school students in grades 1, 2 and 3 using ingredients available around them, and paying attention to safety elements for children. Parents at home can also involve their children in cooking activities at home, even though the children are still in the developmental stage so that cooking tasks at home can be adjusted to the child's development and safety. So that children become more independent and skilled in doing housework, especially cooking.